REPRESENTASI POLITISI PEREMPUAN DALAM FILM THE IRON LADY - GItamaharani Arya, Ni Made Amalika; Amanda Gelgel, Ni Made Ras; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2017)
ABSTRAK Female politicians are often trapped in a condition called double standard that makes them facing difficulty to survive in the world of politics. The struggles of female politician in facing the severity of politics are displayed in a movie called The Iron Lady. The Iron Lady is a movie directed by Phillyda Loyd and played by Meryl Streep. This movie is about one of the most known female politician who were also the Prime Minister of the Great Britain in 1979-1990, Margareth Thatcher. This movie showing the struggle of Margareth Thatcher from her teenage days until she became the Prime Minister from the memories of the old Margareth Thatcher. The Purpose of this research is to know the representation of a female politician from The Iron Lady movie. This research is using qualitative descriptive approach with Peirce’s method of semiotics analysis. The result of this research shows that although The Iron Lady pictured a strong and firm female politician like Margareth Thatcher, this movie is still displaying the feminine side of Thatcher. This movie also shows how a female politicians needs to struggle more to gain recognition, and female politicians also cant get away from the domestic concept of housewives. Keywords : Female Politicians, Film, Representation, Semiotics